Global-scale benefit–cost analysis of coastal flood adaptation to different flood risk drivers using structural measures - Tiggeloven, Timothy; de Moel, Hans; Winsemius, Hessel C.; Eilander, Dirk; Erkens, Gilles; Gebremedhin, Eskedar; Diaz Loaiza, Andres; Kuzma, Samantha; Luo, Tianyi; Iceland, Charles; Bouwman, Arno; van Huijstee, Jolien; et al. (Natural hazards and earth system sciences, 2020)
Coastal flood hazard and exposure are expected to increase over the course of the 21st century, leading to increased coastal flood risk. In order to limit the increase in future risk, or even reduce coastal flood risk, adaptation is necessary. Here, we present a framework to evaluate the future benefits and costs of structural protection measures at the global scale, which accounts for the influence of different flood risk drivers (namely sea-level rise, subsidence, and socioeconomic change). Globally, we find that the estimated expected annual damage (EAD) increases by a factor of 150 between 2010 and 2080 if we assume that no adaptation takes place. We find that 15 countries account for approximately 90 % of this increase. We then explore four different adaptation objectives and find that they all show high potential in cost-effectively reducing (future) coastal flood risk at the global scale. Attributing the total costs for optimal protection standards, we find that sea-level rise contributes the most to the total costs of adaptation. However, the other drivers also play an important role. The results of this study can be used to highlight potential savings through adaptation at the global scale.